Climbing behavior by mice as an endpoint for preclinical assessment of drug effects in the absence and presence of pain - Santos, Edna J.; Giddings, Arianna N.; Kandil, Farah A.; Negus, S. Stevens (Frontiers in Pain Research, 2023)
This study evaluated climbing in mice as a tool to assess the expression and treatment of pain-related behavioral depression in male and female ICR mice. Mice were videotaped during 10-min sessions in a vertical plexiglass cylinder with wire mesh walls, and “Time Climbing” was scored by observers blind to treatments. Initial validation studies demonstrated that baseline climbing was stable across repeated days of testing and depressed by intraperitoneal injection of dilute lactic acid (IP acid) as an acute pain stimulus. Additionally, IP acid-induced depression of climbing was blocked by the positive-control non-steroidal anti-inflammatory drug (NSAID) ketoprofen but not by the negative control kappa opioid receptor agonist U69593. Subsequent studies examined effects of single-molecule opioids (fentanyl, buprenorphine, naltrexone) and of fixed-proportion fentanyl/naltrexone mixtures (10:1, 3.2:1, and 1:1) that vary in their efficacy at the mu opioid receptor (MOR). Opioids administered alone produced a dose- and efficacy-dependent decrease in climbing, and fentanyl/naltrexone-mixture data indicated that climbing in mice is especially sensitive to disruption by even low-efficacy MOR activation. Opioids administered as a pretreatment to IP acid failed to block IP acid-induced depression of climbing. Taken together, these findings support the utility of climbing in mice as an endpoint to evaluate candidate-analgesic effectiveness both to (a) produce undesirable behavioral disruption when the test drug is administered alone, and (b) produce a therapeutic blockade of pain-related behavioral depression. The failure of MOR agonists to block IP acid-induced depression of climbing likely reflects the high sensitivity of climbing to disruption by MOR agonists.